2010
DOI: 10.1002/etc.161
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and a screening‐level risk assessment of human pharmaceuticals in the Pearl River system, South China

Abstract: Ten nonsteroidal antiinflammatory drugs (NSAIDs), two blood lipid regulators (BLRs), and two antiepileptic drugs (AEDs) were analyzed in the Pearl River system in China (i.e., Liuxi, Zhujiang, and Shijing Rivers) and four sewage effluents during the dry and wet seasons, and the environmental risks they posed were assessed. Eight pharmaceuticals were detected in the rivers and effluents, including five NSAIDs (salicylic acid, ibuprofen, diclofenac, mefenamic acid, and naproxen), two BLRs (clofibric acid and gem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(67 citation statements)
references
References 32 publications
5
60
0
2
Order By: Relevance
“…Thus, in addition to application of irrigation water, atmospheric deposition might also contribute to the presence of 4-nonylphenol in the soils (Dachs et al, 1999;Van Ry et al, 2000). For salicylic acid, it was one of the most frequently detected acidic pharmaceuticals in surface waters and sewage effluents (Kasprzyk-Hordern et al, 2008;Matamoros and Bayona, 2006;Peng et al, 2008;Ternes, 1998;Zhao et al, 2010), which could be attributed to the extensive use in human and animals to reduce inflammation. The compound is very mobile as indicated by its physicochemical properties with a high water solubility and low log K ow value (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in addition to application of irrigation water, atmospheric deposition might also contribute to the presence of 4-nonylphenol in the soils (Dachs et al, 1999;Van Ry et al, 2000). For salicylic acid, it was one of the most frequently detected acidic pharmaceuticals in surface waters and sewage effluents (Kasprzyk-Hordern et al, 2008;Matamoros and Bayona, 2006;Peng et al, 2008;Ternes, 1998;Zhao et al, 2010), which could be attributed to the extensive use in human and animals to reduce inflammation. The compound is very mobile as indicated by its physicochemical properties with a high water solubility and low log K ow value (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that concentrations of PPCPs tend to be higher during low water seasons as a result of dilution in the high water season (Xu et al, 2007a;Zhao et al, 2010b;Murata et al, 2011). In this work, surface water samples were collected in winter, corresponding to the low water season in the Yangtze River, and therefore should reflect the upper environmental risks limits.…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%
“…Due to the increasing concern for the potential environmental risks of PPCPs, many studies were carried out in China to study their occurrence, fate, and effects in the environment. PPCP residues have been reported in the Pearl River Delta (Peng et al, 2008;Zhao et al, 2010b), Yellow River (Zhou et al, 2011;Zou et al, 2011), Yangtze River estuary (Yan et al, 2013), offshore areas of the Bohai Sea and Yellow Sea , and the Yongjiang River (Xue et al, 2013). Xu et al (2007b) and Sui et al (2010) studied the occurrence and removal of PPCPs in wastewater treatment plants in China.…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, the antibiotic concentrations such as Oxytetracyclin, Trimethoprim and Sulfamethoxazole are high in both wastewater influent effluent and surface water [10]. In additional, researcher analyzed for 10 NSAIDs, 2 blood lipid regulators, and 2 antiepileptic drugs in the Pearl River system in China (Liuxi, Zhujiang, and Shijin Rivers) and four sewage effluents during the dry and wet seasons, results were reported and the environmental risks they posed were assessed [11]. Other in China, river water and tap water screened for the presence of β-lactam antibiotics.…”
Section: Surface Watermentioning
confidence: 99%